2021
DOI: 10.1002/rcr2.832
|View full text |Cite
|
Sign up to set email alerts
|

A case of giant intradiaphragmatic bronchogenic cyst

Abstract: We present the case of a giant bronchogenic cyst (BC) that appeared just within the right diaphragm. A 51‐year‐old man was referred to our hospital with a chief complaint of pain from the lumbar area to the right shoulder. Computed tomography images showed a cystic mass measuring 18.0 × 17.5 × 12.8 cm in the right thoracic cavity. Right posterolateral thoracotomy from the eighth intercostal space was performed, and the cyst wall and diaphragm were resected together. The defect of the diaphragm was repaired usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Ectopic BCs are very uncommon and even rarer than the intradiaphragmatic ones. Diaphragmatic BCs typically occur on the left, in women and in the vertebra-phrenic angle 2 8 9. In a recent report, Tang et al 1 stated that 24 ectopic BCs have been reported in the past 15 years, of which only 3 (including theirs) were diaphragmatic.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic BCs are very uncommon and even rarer than the intradiaphragmatic ones. Diaphragmatic BCs typically occur on the left, in women and in the vertebra-phrenic angle 2 8 9. In a recent report, Tang et al 1 stated that 24 ectopic BCs have been reported in the past 15 years, of which only 3 (including theirs) were diaphragmatic.…”
Section: Discussionmentioning
confidence: 99%